Upaya Pencegahan Kanker Kolorektal pada RemajaSMK Kesehatan Rajawali - Theophylia Melisa Manumara; Rifan Abiansyah; Sintia Dian Ningsih; Nahla Fauziah Sukmana; Nazma Septia Wanty; Aulia Suci Ajeng Putri Lestari; Siti Sofiah; Sinta Sulistiawati; Bakhi Fadlah; Chalisa Putri Mayda; Maritha Aurin Alfarizki (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
Colorectal cancer is a noncommunicable disease with an incidence rate that continues to rise in various countries, including among younger age groups. Unhealthy lifestyle behaviors among adolescents, such as low fiber intake, high consumption of fast food, lack of physical activity, and low health awareness, contribute to an increased risk of colorectal cancer at a young age. Prevention efforts through health education are crucial for fostering healthy lifestyle behaviors starting in adolescence. This community health education program aims to enhance the knowledge and awareness of students at Rajawali Health Vocational School regarding colorectal cancer prevention. The methods employed include interactive health education through lectures, discussions, Q&A sessions, educational games, and the use of supporting materials such as leaflets and PowerPoint presentations. Evaluation was conducted using pre-tests and post-tests to measure changes in participants’ knowledge levels. The program involved 35 students as participants. The results of the activity showed an increase in students’ understanding of the definition of colorectal cancer, risk factors, early signs and symptoms, the importance of adopting a healthy lifestyle, and efforts toward early detection. Participants also demonstrated active participation and enthusiasm throughout the event. Interactive health education methods have proven effective in increasing adolescents’ knowledge and awareness of colorectal cancer prevention and in fostering healthy lifestyle habits from an early age.